PERFORMANS DAN KOMPOSISI KARKAS BABI BALI BETINA MUDA YANG DIBERI RANSUM DENGAN SUPLEMENTASI PROBIOTIK - Wibawa I. M. S. P.; K. Budaarsa; I G. Mahardika (Fakultas Peternakan Universitas Udayana, 2019)
This study aims at determining the performance and carcasses composition of young female pig which arereared intensively and fed good quality rations and probiotic supplementation Saccharomyces sp. This researchwas conducted at Experimental Laboratory, Faculty of Animal Science, Udayana University, Bukit, Jimbaran. Thedesign using a randomized block design (RBD) with basic weighting grouping. This design is used randomly groupedin basic body weight. The bali pigs were allocated randomly into four treatments i.e. ration without additionalprobiotics (A), ration with 0.20% additional probiotics (B), ration with 0.25% additional probiotics (C), and rationwith 0.30% additional probiotics (D). The treatments were conducted in 4 times replication so there are 16 pigsand kept in individual pens. The variables observed were the performance and composition of carcass. Based onthe results, ration consumption, additional of body weight, FCR, digestibility rations and carcasses compositionshowed not significant differences. It can be concluded that the additional of probiotics in the ration of youngfemale Bali pigs did not effect to the variable performance and carcass characteristic up to 0.30% addition level.